Todays’ Assessment: Between Traditional and Alternative Assessment - Aisyah Nurjanah (Jurnal Syntax Transformation, 2026)
Assessment plays a pivotal role in EFL (English as a Foreign Language) instruction, yet Indonesian teachers continue to struggle with designing valid, reliable, and pedagogically appropriate instruments—defaulting to traditional formats that inadequately capture learners' productive language skills. Despite a growing body of literature on alternative assessment, an integrated comparative analysis of how both assessment paradigms are simultaneously implemented in Indonesian school contexts remains underexplored. This study employs a qualitative library-research design. Data were collected through systematic documentation of peer-reviewed journal articles, book chapters, and policy documents relevant to traditional and alternative assessment practice in EFL settings. Thematic content analysis was applied to synthesize findings across sources. The analysis reveals that Indonesian EFL classrooms predominantly rely on traditional assessment tools (tests, quizzes, gap-filling, MCQs) due to their administrative simplicity. Alternative assessments—particularly portfolio and performance-based tasks—are present but limited by teachers' low assessment literacy, time constraints, and the absence of institutional support. The coexistence of both paradigms reflects a transitional assessment culture shaped by curriculum reform pressures. This study uniquely synthesizes findings from both global and Indonesian-specific sources to construct a comparative evaluative framework that connects assessment type, teacher competency, and student learning outcomes in EFL contexts, offering actionable implications for teacher professional development and curriculum policy.